The analysis of macroeconomic gaps in Iraq for the period (1990-2017) - Kamil Rasheed, Mustafa (Opción, 2020)
The study aims to investigate the analysis of macroeconomic gaps in Iraq between 1990 to 2017 via comparative quantitative research methods. As a result, inflation rates at zero limits except for some years such as 1991 because of the new monetary issue caused a sharp rise in prices. In conclusion, investment remains weak both public and private, as well as the erosion of infrastructure in security-stable governorates and their destruction in unstable security governorates.